Nanosilica-mediated plant growth and environmental stress tolerance in plants: mechanisms of action - de Souza Júnior, Jonas Pereira [UNESP]; de Mello Prado, Renato [UNESP]; Campos, Cid Naudi Silva; Teixeira, Gelza Carliane Marques [UNESP]; Ferreira, Patrícia Messias [UNESP] (Elsevier, 2022)
Nanosilica consists of silicon dioxide (SiO2) nanoparticles in colloidal dispersion, with different physicochemical characteristics from those of nonnanoparticulate matter, due to their small size, usually less than 100nm, varying shapes and large surface area. Nano-SiO2, an important nanomaterial used in the field, is efficient in raising shoot Si content owing to its hydrophilic properties, which allow easy absorption. This Si source has also shown high stability in solution, with low polymerization, a limiting factor for the use of silicate sources in leaf applications. After being absorbed, a large part of the Si is deposited in leaf cells forming a double layer of cuticle-silicon-cuticle, which causes important morphological changes for a plant, increasing its tolerance to environmental stress. However, recent studies indicate that part of Si is not incorporated into the structure of plants, and it results in biochemical and physiological changes, which increase the defense mechanisms of plants against environmental stress. This chapter will present the results of innovative studies on the use of Si in nanoparticle form, how it modifies the morphology, biochemistry, and physiology of plants, and how these changes contribute to mitigating the harmful effects of environmental stress.
Keywords: antioxidant systems; Beneficial element; biochemical changes; morphological changes; oxidative stress; photosynthesis; physiological changes